Analisis Potensi Kawasan Makam Gus Dur Sebagai Halal Tourism - Marwati, Niken (Jurnal Manajemen Dakwah, 2023)
The purpose of this study is to examine the potential of Gus Dur's grave as a halal tourism destination, including its cultural, historical, and religious aspects that can attract tourists. This study uses qualitative method research with a descriptive approach.  Data collection techniques include interviews, observation, and documentation. The results showed that the Guis Duir cemetery area has many provinces that can be balanced both from the Attraction, Ameinitieis, and Acceisbility seigi. In addition, Gus Dur's grave area has a strategic location, not only including eiduication tourism, temple tourism, shopping tourism, but also religious tourism that exists today. The existence of infrastructure that supports the Guis Duir cemetery area, namely having a very large parking lot so that people who want to park do not have problems parking the vehicles they bring.